Metabolomic analysis and antibacterial and antioxidant activities of three species of Artemisia plants in Tibet - Liu, Xinyu; Renzengwangdui; Tang, Shiyu; Zhu, Yiru; Wang, Meng; Cao, Binqian; Wang, Jinglong; Zhao, Baoyu; Lu, Hao (BMC plant biology, 2023)
Artemisia is important medicinal plants in China and are widely used in medicine, agriculture, and food. Pharmacologically active components of the plants remain to be investigated. This study sought to identify and compare the chemical constituents of three species of Artemisia in Tibet using a widely-targeted metabolomics approach and their antibacterial and antioxidant capacities were determined. A total of 1109 metabolites within 10 categories were detected from the three species of Artemisia, including lipids, amino acids, nucleotides, flavonoids, terpenes, coumarins, organic acids, and phenolic acids. 732 different metabolites have been identified between Artemisia sieversiana and Artemisia annua, 751 different metabolites were identified between Artemisia wellbyi and A. sieversiana, and 768 differential metabolites were differentially detected from A. wellbyi and A. annua. Differentially identified compounds included flavonoids, phenolic acids, artemisinins and coumarin. A. annua contained the highest relative content of artemisinin among three Artemisia. The antimicrobial experiments showed that the three Artemisia species had strong antibiotic activities against Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Proteus mirabilis and Pseudomonas aeruginosa. The biochemical analysis showed that the three species of Artemisia have strong antioxidant capacity. This is the first reported attempt to comparatively determine the types of the metabolites of the three widely distributed Artemisia species in Tibet. The information should help medicinal research and facilitate comprehensive development and utilization of Artemisia species in Tibet.